Perancangan Dan Pembuatan Sistem Kontrol Penggerak Torch Potong Las Oxy-Acetylene Berulir Berbasis Mikrokontroler Arduino Uno - Handoko, Yulli; Herisiswanto, Herisiswanto; Syafri, Syafri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Currently, the most common method of cutting steel is cutting with oxygen gas. Because the cutting method with manual cutting produces poor results and complicated processes. This plate cutting tool is made to facilitate the work especially in the field of construction. The used research method is based on the workprinciple of CNC 2 axis machine, because it is able to move in the direction of X and Y axis on the work plane, also has a hight accurancy and precision. This plate cutting tool use 3 Softwares, i.e Universal G-Code Sender as a controller, QCAD as a workpiece design and DXF2G-CODE as a code exporter. The manufacture ofmicrocontroller-based plate cutting tool results an easier plate cutting process, because the operator have to input the data according to the necessary only. From the X and Y axis movement and plate cutting velocity testing, the result data has equal magnitude between the program, simulation and actual condition.Key Words : Oxy-Cutting, Microcontroller, Arduino UNO.